Ultrasound-assisted leaching of vanadium from fly ash using lemon juice organic acids. Issue 3 (10th January 2020) - Rahimi, G.; Rastegar, S. O.; Rahmani Chianeh, F.; Gu, T.
Abstract : In this work, vanadium (V) was selectively extracted from fuel-oil fly ash using a leaching process utilizing organic acids extracted from lemon juice with assistance from ultrasound and H2 O2 . Abstract : In this work, vanadium (V) was selectively extracted from fuel-oil fly ash using a leaching process utilizing organic acids extracted from lemon juice with assistance from ultrasound and H2 O2 . Response Surface Methodology (RSM) was used to optimize the main operating factors. The V recovery was 88.7% at the optimal conditions: 27.9% (v/v) lemon juice, 10% (v/v) hydrogen peroxide (H2 O2 ), solid/liquid (S/L) ratio 0.01% (w/v), ultrasound power 159 W at 20 kHz in 2 h, and initial temperature of 35 °C. The effect of time on the V recovery was examined. The maximum recovery was 100% after 3 h. Furthermore, the individual effects of ultrasound and H2 O2 on V recovery were studied, and the results showed that without H2 O2 and ultrasound, the V recovery decreased greatly, indicating that both factors were essential in the leaching process. According to the modified shrinking core model, test results indicated that mass diffusion was the controlling step of the overall reaction kinetics. The activation energy of the leaching reaction in the temperature range 25 to 65 °C was found to be 17.1 kJ mol −1 .